DAMPAK PEMBERIAN TAMBAHAN PENGHASILAN PADA KINERJA PEGAWAI NEGERI SIPIL ( STUDI PADA KANTOR CAMAT NGEBEL KABUPATEN PONOROGO ) - Windari, Windari (JI@P, 2021)
The purpose of the study to find out and analyze the impact of the provision of Additional Income on the performance of Civil Servants in the Office of The District Head of Ngebel Ponorogo.Qualitative descriptive research type. Research objects are based on people's data sources, documents and events.Selection of informants with purposive sampling techniques. Interview, observation and documentation data collection techniques. Data instruments in the form of a list of questions, observations and recordings. Data analysis techniques using interactive data analysis of miles &huberman models. The impact was analyzed with Finsterbusch theory and Motz Single before-after program according to and performance theory according to John Miner with indicators of quality, quantity, use of time in work and cooperation.The results showed that the implementation of AEI was going well but there were still technical constraints.Quality there is an improvement in the quality of the work and a decrease in the error rate although not too great.The positive impact on the quantity of budget realization efficiency and realization of organizational performance achievement exceeds the target above 100%.The use of time in work there is a decrease in violations of working hours at the rate of absence, the rate of delay and quick return.The effective working time of employees in 2020 averaged 85%. While in the aspect of cooperation is not seen the impact because it has been running well before the AEI.